SERVICE QUALITY TOWARDS STUDENT’S SATISFACTION AT ACADEMIC ADMINISTRATION AND STUDENTS AFFAIRS DEPARTMENT (AASA) - Sanjaya Stephen Prischou; Suzetta Feby (JURNAL RISET MANAJEMEN (JURMA), 2023)
. Based on the above problem, then this study was held in order to know the influence of service quality in AASA to student’s satisfaction. The method used in this study was multiple linear regression analysis which measures the influence of service quality in AASA section to the satisfaction of the students of Institute of Business and Informatics STIKOM Surabaya and which factors of the dimensions of service quality that need to be improved. Service quality dimensions include Tangible, Reliability, Responsiveness, Assurance, and Empathy. The results obtained are the dimensions of Reliability and Responsiveness have no effect on student’s satisfaction, while the dimensions of Tangible, Assurance, Empathy of service quality have a positive effect on student’s satisfaction at Institute of Business and Informatics by 63% which has a meaning that any increase of physical display dimensions, assurance, and empathy will increase student’ssatisfaction . Based on the results of the descriptive analysis, it is found that "AASA staff performance that has been neat and attractive" still needs to be improved, while other indicators of service quality tends to be very good, so it needs to be maintained.